PERAN DAN FUNGSI SOSIAL MASJID DALAM MENINGKATKAN KUALITAS KEAGAMAAN MASYARAKAT DESA PALALANGAN - SUTRIYONO SUTRIYONO (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2021)
The mosque is a vital tool for Muslims in carrying out daily, weekly, and annual ritual worship. The mosque is a symbol of Islamic civilization. In essence, mosques can function as social facilities to mobilize, empower, and improve the quality of society. The sacredness of the mosque as the center of a place of worship in an area becomes a magnet in itself and can be used as capital in improving the quality of mosque congregations through activities with transcendental spiritual nuances. This study discusses the role and social function of the mosque as part of the religious system and social institutions. This type of research is field research with a qualitative approach. The results of the study indicate that the mosque can carry out its social roles and functions well as a center for community religious activities.